Smart coffee vending machine based on IoT concept - Pongswatd, Sawai; Smerpitak, Krit; Thepmanee, Teerawat (My University, 2020)
In order to improve the effectiveness of franchise system, this paper describes how to utilize the Internet of Things (IoT) concept for upgrading a franchisor’s traditional coffee vending machine to be a smart coffee vending machine (SCVM) with remote monitoring and control capabilities. The IoT-based SCVM provides powerful web dashboard to monitor machine operation statuses, track ingredient and component availability, and adjust hot drink recipes. The proposed improvement can therefore help both franchisor and franchisee not only to ensure that how well the machine is operating, and how well the machine is stocked but also to plan that when a supply worker needs to pay a visit to the machine for refilling ingredients based on sales data, and when a maintenance worker needs to pay a visit to the machine for providing services based on technical data. The proposed technique uses an Arduino board to replace an existing machine controller and installs a Raspberry Pi module to perform as a gateway for data transmission between the SCVM and the Ubidots cloud server via Internet. The Node-RED engine running on the Raspberry Pi is utilized as the IoT platform to collect and process the technical and sales data of the SCVM that dispenses three kinds of hot drinks. Based on user login system, the franchisor is allowed to remotely monitor the interested parameters of all SCVMs on the created dashboard for ensuring product availability as well as to remotely control the ratios of instant coffee/cocoa powder and hot water for ensuring product quality, whereas each franchisee is allowed to remotely monitor the operation status and daily sales detail for his approved machines only. Test results from data simulations confirm that the upgraded SCVM and created dashboard subpages function correctly in accordance with the franchisor’s requirements.
Keywords: Arduinoboard; Coffeevendingmachine; Dashboard; Franchisesystem; IoT; Raspberry Pi module; Ubidots cloud service